Quantum shadows - Modesitt, L. E., Jr., 1943- (Tor, 2020)
On a world called Heaven, Conwyn, known as the Shadow of the Raven, contains the collective memory of humanity's Falls from Grace and discovers that another Fall may happen and if he doesn't stop it, mankind will not survive.